Islamic Knowledge And Attitudes Toward Hiv/Aids Among Undergraduates In UPM Serdang - Hanina Halimatussaidiyah Hamsan; Lee Mei Siah (AL-FIKRA, 2017)
Research has been conducted attitudes related HIV/AIDS issue particularly among university students because students are the group of younger generation that may be parents advising their children in future or they may have to contact with HIV  infected and AIDS people in their future work.  The purpose of research design is to identify the most economical method in conducting the research. The non- experimental quantitative research design which is in questionnaire tools has used to finalize results that are based on hypothesis testingThe population of this study is targeted to the undergraduates from Human Ecology in UPM, Serdang. The sample size for the study is determined by the calculation formula (Israel, 2009). The minimum sample size for FEM is approximately 271, which is calculated by the formula of known population size (N = 835) with the 95% confidence level and confidence interval of 5%.to achieve the objectives for this current study. Besides, three techniques of research design are descriptive, correlation and comparative also have been chosen in this study.  Descriptive design is used to gather the quantitative information and then organizes, tabulates, depicts, and describes the data collection. Descriptive involved in this study will be given a general description about respondent’s personal characteristic (gender), level of knowledge in HIV/AIDS and attitudes toward HIV/AIDS.  The correlation design is applied to determine the linear relationship between personal characteristic (gender), knowledge and attitudes towards HIV/AIDS among FEM undergraduates. The result of the correlation can be positive and negative. If the result is positive correlation, then the changes in value of one variable will make the changes of the other variables in the same direction, or vice versa.